From molecular damage and viscoelasticity to interfacial fracture in soft polymer networks: Insights from mechanochemistry - Anthony Arrowood; Jackson Frazier; Matteo Ciccotti; Gabriel E. Sanoja (Proceedings of the National Academy of Sciences, 2025)
Many soft, tough materials have emerged in recent years, paving the way for advances in wearable electronics, soft robotics, and flexible displays. However, understanding the interfacial fracture behavior of these materials remains a significant challenge, owing to the difficulty of quantifying the respective contributions from viscoelasticity and damage to energy dissipation ahead of cracks. This work aims to address this challenge by labeling a series of polymer networks with fluorogenic mechanophores, subjecting them to T-peel tests at various rates and temperatures, and quantifying their force-induced damage using a confocal microscope. The results challenge longstanding assumptions underlying linear viscoelastic fracture theories, revealing a complex interplay between viscoelasticity and damage governed by the Weissenberg number, W i . Specifically, they suggest a molecular picture in which the interfacial toughness increases due to polymer chain breakage and enlarged strains when W i < 0.3 , and significant chain friction and network stiffening when W i > 0.3 , with the damage being negligible in the limits of W i ≪ 0.3 and W i ≫ 0.3 either due to insufficient strains at the peel front or because of excessive stress at weak interfacial bonds. Overall, these results illustrate the molecular and mesoscopic mechanisms underpinning interfacial fracture, aiding to refine current viscoelastic fracture theories and accelerating the development of advanced polymer networks for increasingly demanding applications.